PELATIHAN PEMASARAN PRODUK UMKM “REMOJONG” BERBASIS INTERNET DI KABUPATEN BREBES - Andi Yulianto; Roby Setiabudi; Agyztia Premana (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
"Remojong" is one of the UMKM associations in Brebes Regency. "Remojong" itself is taken from the Brebes language which means synergizing together or in mutual cooperation. This association aims to embrace all perpetrators of SMEs originating and native to Brebes spread throughout Indonesia. Some of the products in the "Remojong" MSME are already exported abroad, such as Malaysia, Singapore, and Saudi Arabia. However, there are also products that have not been able to be marketed outside the city outside the Brebes area. So that the problem encountered in the field is the weak use of technology in this case the internet to market MSME products. So that the business of MSME actors is stagnant, does not lose but does not grow optimally. The purpose of this community service will only discuss the marketing problems experienced by the "Remojong" MSME actors in Brebes Regency. The products owned by MSME players "Remojong" are very feasible to compete with other products. However, due to problems with marketing, product development was hampered due to poor marketing management. From the community service activities that have been carried out, it can be concluded that the knowledge and understanding of the Brebes "Remojong" MSME actors has increased regarding product marketing strategies through Facebook social media. This can be seen from the indicators of the number of questions asked by participants and explanations related to them, so there is a good transfer of information and an increase in understanding related to how to market MSME products.